Gender Differences in Language Acquisition Patterns among Adolescents in Japan - Tanaka, Ayaka (International Journal of Linguistics, 2024)
Purpose: The aim of the study was to analyze the gender differences in language acquisition patterns among adolescents in Japan Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: This study examines gender differences in language acquisition among Japanese adolescents. Males typically prefer informal methods like digital media for vocabulary, while females favor formal instruction. Females show stronger syntax, grammar, and pragmatic skills, driven by a greater interest in language learning for social reasons. Males' attitudes vary more, influenced by socioeconomic factors. Unique Contribution to Theory, Practice and Policy: Social learning theory, gender schema theory & critical feminist theory may be used to anchor future studies on the gender differences in language acquisition patterns among adolescents. By tailoring language instruction to the specific needs of male and female adolescents, educators can create more inclusive learning environments that support equitable language development. Policymakers should prioritize the integration of gender-sensitive language policies and initiatives within educational systems.